Reference with the Pronoun in Surat Yassin: A Study of Textual Cohesion according to Van Dijk’s Model of Textual Analysis - yousif, shafaq (Al-Adab Journal, 2020)
This research sheds light on the function of the pronoun as a tool of textual cohesion in Surat Yassin, based from theoretical and procedural perspectives on the model of textual analysis for Teun A. Van Dijk, who has laid the foundations for a pragmatic syntactic approach in understanding the text and analyzing it in a syntactic manner, and by adopting constructive statements of a total nature, the most important of which is the " Macro structure". Depending on this, the analysis of the surat text, on the deep thematic level reveals the effects of the textual unity of the surat in spite of the multiplicity in the theme patterns in the text, by showing the primary function of pronoun reference: providing the semantic tool that serves the cohesion of the text, and, carries its thematic structure